Pengaruh Pemberian Kompres Es Batu Terhadap Penurunan Tingkat Nyeri Pada Anak Usia Pra Sekolah yang Dilakukan Prosedur Pemasangan Infus di RSUPN Dr. Cipto Mangunkusumo Jakarta - Endah Sulistiyani (STIKES Mataram, 2015)
Distress is a negative effect during hospitalization on children. Invasive procedures, separation anxiety and painful which cause considerable child distress. Invasive procedures during hospitalization continuesly distress. Intrusive procedures such as venipuncture are Well understood as a stressfull event for children. Pain management were pharmacological and non pharmacological. Cutaneus stimulation is a non pharmacological theraphy to reduce venipuncture related pain and can be performed by nurses. Ice cube is cutaneus stimulation. The purpose ofthis study was determining the effect of ice cube prior to venipuncture on pain related responses in preschool age child. This study is quasi experiment with nonequivalent control group after only design. The subject were 64 preschool child selected by purposive sampling. Two groups were chosen for this study: 32 the test and 32 control group. Pain responses were measured using Wong Baker faces Pain Scale and confounding factor were measured using quesionaire. After homogeneity test this study analyzed with chi square. Result showed that ice cube reduced pain on preschool age child who were venipuncture, 813% mild pain with ice cube and I6, 7% mild pain Without ice cube onp:0. 01, a <0, 05. Ice cube efficient and effective for cutaneus stimulation. Pediatric nurse could apply ice cubefor atraumatic care on venipuncture procedures. Sex, ethnic, member offamily present, and child experience did not effect pain relieve in chidren. Child fear significantly effect for pain relieve in preschool ege child.Key word : ice cube, pain management, pain scale, venipuctur references : 41 ( 1995 2009 )